Photocatalytic Activity of Synthetic N‐doped TiO2/Reduced Graphene Oxide Crystalline Composites. Issue 7 (13th June 2017) - Chen, Jianxin; Wang, Xinxin; Li, Yinhui; Zhang, Na; Su, Min; Han, Jian
Abstract: N‐doped TiO2 /reduced graphene oxide (N‐TiO2 /RGO) composites were prepared by a hydrothermal method. Characterization and photocatalytic tests showed that the N‐TiO2 /RGO composites were more efficient for degrading effluents in comparison with the pure TiO2 powders and the N‐doped TiO2 powders. The photocatalytic performance of the composites was enhanced with the increase of the reduced graphene oxides' content, whose degradation rate constant was higher than that of N‐TiO2 under simulated sunlight irradiation. After five successive cycles, 50 % N‐TiO2 /RGO still exhibited high activity, which indicates that the composites are stable under irradiation. An innovative strategy for the exploration of advanced photocatalysts in wastewater treatment is provided. Abstract : A strategy for analysis of advanced photocatalysts in wastewater treatment is proposed. Electrons are excited from the valence band to the conduction band to form photogenerated electrons, leaving holes in the valence band. Such electrons are transferred to the surface of graphene which reduces the recombination rate of photogenerated electrons and holes and improves the photocatalytic efficiency.